Aphrodisiac Effect of Ethanol Extract of Tapak Liman (Elephantopus scaber L.) Leaves on Testosterone Levels and Testicular Histology in Rats - Saristiana, Yuneka; Salmasfattah, Novyananda; Prasetyawan, Fendy; Savitri, Lisa (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2025)
The demand for aphrodisiac use is substantial, however, many marketed herbal products contain synthetic drugs, underscoring the urgent need for safer natural therapeutic alternatives. This study aimed to evaluate the aphrodisiac potential of ethanol extract of Elephantopus scaber (Tapak Liman) leaves on serum testosterone levels and testicular histology in male Wistar rats. The extract was obtained through maceration with 70% ethanol and subjected to phytochemical screening, which revealed the presence of flavonoids, tannins/phenolics, and triterpenoids. Healthy male Wistar rats were divided into five groups: normal control, negative control, positive control (sildenafil), and two treatment groups receiving 100 mg/kg BW and 200 mg/kg BW of the extract for 21 days. Serum testosterone levels were measured using ELISA, while histological examination focused on the diameter of seminiferous tubules. The results demonstrated that the 200 mg/kg BW dose significantly increased testosterone levels (209.41 ± 0.62 ng/dL) compared with the negative control (120.32 ± 1.55 ng/dL) and restored the diameter of seminiferous tubules (220.56 ± 4.98 µm) close to normal conditions (225.30 ± 5.12 µm). The 100 mg/kg BW dose produced a moderate effect, while the positive control also showed notable improvement. The observed increase in testosterone and recovery of seminiferous tubule diameter indicate that the extract enhances spermatogenic activity and testicular function. In conclusion, the ethanol extract of E. scaber leaves at 200 mg/kg BW demonstrated significant aphrodisiac activity through hormonal stimulation and improvement of testicular histology, suggesting its potential as a natural agent to support male reproductive health.